2011
DOI: 10.1186/1475-925x-10-6
|View full text |Cite
|
Sign up to set email alerts
|

Antepartum fetal heart rate feature extraction and classification using empirical mode decomposition and support vector machine

Abstract: BackgroundCardiotocography (CTG) is the most widely used tool for fetal surveillance. The visual analysis of fetal heart rate (FHR) traces largely depends on the expertise and experience of the clinician involved. Several approaches have been proposed for the effective interpretation of FHR. In this paper, a new approach for FHR feature extraction based on empirical mode decomposition (EMD) is proposed, which was used along with support vector machine (SVM) for the classification of FHR recordings as 'normal' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 45 publications
0
47
0
1
Order By: Relevance
“…A predictive fetal heart rate record is the principle indication that led to intervention and delivery. A prediction of fetal asphyxia that leads to intervention and delivery may prevent or modify moderate or severe newborn morbidity as the result of fetal asphyxia 13 .…”
Section: Introductionmentioning
confidence: 99%
“…A predictive fetal heart rate record is the principle indication that led to intervention and delivery. A prediction of fetal asphyxia that leads to intervention and delivery may prevent or modify moderate or severe newborn morbidity as the result of fetal asphyxia 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Huang [42] analyzed the CTG data by three machine learning methods to create the classification models to predict fetal distress. Krupa et al [43] suggested using statistical features extracted from empirical mode decomposition (EMD). The extracted features from the decomposed components classified as normal and at risk.…”
Section: Discussionmentioning
confidence: 99%
“…Some have combined empirical mode decomposition (EMD) and support vector machines (SVM). This actually resulted in a test accuracy of 86% [22].…”
Section: Methodsmentioning
confidence: 99%